Coping with Trouble: How Science Reacts to Political Disturbances of Research Conditions - Uwe Schimank; Andreas Stucke (Campus Verlag; Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V., 1994)
Manifold political interventions, such as resource cutbacks, political regulation and societal instrumentalization of research, are frequently viewed by today's scientists and research institutes as trouble which must be coped with. Approaching the sociology of science from an institutionalist perspective, the editors introduce the concept of "Coping with Trouble". The case studies examine scientists' efforts to cope, emphasizing the complexity of actor constellations and the mutual interference between coping reactions. Finally, in a comparative analysis of its undesirable and unintended results, the editors explain why coping is often ineffective and insufficient.
hdl:11858/00-001M-0000-0012-5A4C-1
Keywords: 300